(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Differences Â in Â marketing Â strategies Â with Â other Â industries Â are Â needed Â to maintain Â business Â sustainability Â especially Â for Â facing Â fierce Â market Â competition. This Â research Â was Â aimed Â to Â identify Â a Â marketing Â mix Â implemented Â in Â micro Â and small Â scale Â coffee Â industries, Â and Â to Â identify Â external Â factors Â that Â affected Â business sustainability. Â This Â study Â was Â carried Â out Â in Â Sumberwringin Â Sub-district, Bondowoso Â District, Â East Â Java. Â Respondents Â of Â this Â study Â were Â 25 Â coffee Â industry players Â selected Â by Â using Â judgement Â sampling Â method. Â Primary Â and Â secondary data Â were Â collected Â in Â this Â study. Â Data Â were Â analyzed Â with Â descriptive-qualitative method Â and Â interactive Â analysis. Â The Â results Â showed Â that Â micro Â and Â small-scale coffee industries was still implementing conventional Â marketing pattern. The marketing mix Â which Â applied Â in Â coffee Â industry, Â were Â (a) Â the Â product Â mix Â was Â not Â persistent that Â depended Â on Â consumer Â demand; Â (b) Â selling Â price Â of Â product Â was Â determined from Â cost Â production Â and Â profit Â margins; Â (c) Â distribution Â was Â conducted Â with active Â and Â passive Â marketing Â particularly Â based Â on Â customer Â orders; Â (d) Â promotion mix Â was Â implemented Â by Â direct Â marketing, Â personal Â selling, Â and Â word Â of Â mouth. Micro-environments of the marketing affecting micro and small-scale coffee industries were: (a) customers as main target market Â in form Â of consumer markets and Â alternative target Â market Â as Â re-seller Â markets; Â (b) Â high Â intensity Â competition Â as Â a Â result of Â large Â number of Â competitors Â and Â lack Â of Â product Â diversification; Â (c) Â many Â raw material suppliers, but expensive Â input Â production Â cost; (d) there was no a marketing partnership Â with Â marketer Â agent/other Â partner, Â but Â it Â had Â strategic Â partnership with Â supplier Â and Â government; Â (e) Â government Â policies Â on Â product Â development and Â marketing Â had Â been Â implemented Â by Â facilitating Â exhibition Â activity, Â processing equipment, Â and Â training.